Design and Manufacture an Automatic Mushroom Sprinkler based Internet of Things to Increase Oyster Mushroom Productivity - Setiawan, Rizal Justian; Tarnadi, Adi; Surfani, Ilham (JMPM (Jurnal Material dan Proses Manufaktur), 2021)
Oyster mushroom is one of the non-cholesterol food ingredients that have high nutrition and high demand by the public. In addition, oyster mushroom has a much cheaper price than chicken and beef. In the cultivation of oyster mushrooms, temperature and humidity are important factors in the success of cultivation, the optimum temperature for the growth of oyster mushrooms is 16-25°C and the ideal humidity required is 80%-90%. To maintain the temperature and humidity is to do watering or misting. Currently, there are still many farmers who use conventional watering systems that are not practical. Therefore, during the dry season, the productivity of oyster mushrooms tends to decrease due to hot weather conditions and intense watering needs to be done. Based on this, it is necessary to develop an automatic and efficient mushroom watering tool. The research method used is Research and Development (RD). The result achieved is the design of an automatic mushroom sprinkler based on temperature and humidity control. This automatic mushroom sprinkler has a blower component, piezoelectric, ATMega 16 microcontroller, DHT11 temperature sensor, and internet of things (IoT) features. The conclusion of this research is the creation of an automatic mushroom sprinkler that is efficient and easy to use. In addition, the results of the implementation of this tool in the cultivation area can increase the productivity of oyster mushrooms by 34.51%.